A Comparative Analysis of Surgical Wound Infection Methods: Predictive Values of the CDC, ASEPSIS, and Southampton Scoring Systems in Evaluating Breast Reconstruction Surgical Site Infections. Issue 2 (May 2019) - Campwala, Insiyah; Unsell, Kayla; Gupta, Subhas
Infection is the most significant complication in breast reconstruction surgery. While the Center for Disease Control and Prevention (CDC) is the most prevalent tool for surgical site infection (SSI) diagnosis, ASEPSIS and Southampton scoring methods have been speculated to be more sensitive. The ASEPSIS scoring system previously demonstrated much better interrater reliability than the CDC. We sought to assess the predictive value of various wound scoring methods in breast reconstruction SSIs. A retrospective analysis of all single-institution breast reconstruction infections from January 2013 to June 2016 was performed. Patients' postoperative wound-related complications were collected. Southampton, CDC, and modified ASEPSIS scores—extended to 30 postoperative days—were calculated. Relative predictive values for implant-based reconstruction were evaluated. Among the 22 reviewed cases, ASEPSIS scores greater than 30 resulted in a more than 50% rate of implant-based breast reconstruction failure. There was a significant positive correlation between ASEPSIS score and failure rate ( P = .022). A Southampton classification of B—minor complication (60% failure)—had a greater associative risk of reconstruction failure than a classification of C—major complication (23% failure)—or classification of D—major hematoma (0% failure). The CDC score had no predictive value of success versus failure of reconstruction. While the CDC criteria and Southampton scoring systems demonstrated little clinical use, the ASEPSIS scoring system shows substantial predictive value for breast reconstruction SSIs. New procedure protocols should be implemented to require detailed surgical notes including the proportion of the wounds affected by inflammatory responses to allow for easier wound score calculation by these alternate scoring systems.